EFL Teachers’ Soft-Skill Strategies in Teaching Speaking - Ni Putu Astrini; Edi Firman (Borneo Educational Journal (Borju), 2021)
Some learners get difficulties in speaking English because of a weak soft-skill they have, such as motivation, social skill, and self-efficacy. Therefore, teachers’ role in embedding soft-skill in teaching speaking is essential because learning success is influenced more by soft-skill than IQ. This study discussed kinds of soft-skills embedded by teachers in teaching speaking. This study uses qualitative analysis approach by using descriptive research design. The data are gained from three English teachers of SMAN 6 MATARAM by observation and interview. The results revealed that there are five kinds of soft--skills embedded by EFL teachers, such as self-perceptions, motivation, creativity, metacognitive and social competencies. Moreover, the steps teacher embed them are by using classroom discussion, giving reward, telling story or information, ordering students to describe a picture in front of class, ordering students to perform dialogue, and sometimes teacher use the same steps in the next meeting if the previous materials have not finished. Those soft-skills contributed to the students’ speaking ability, such as making them more interactive, more communicative and used more various language.